2010
DOI: 10.1007/s11669-010-9806-5
|View full text |Cite
|
Sign up to set email alerts
|

DSC Study of Solid-Liquid Equilibria for Energetic Binary Mixtures of Methylnitramine with 2,4-Dinitro-2,4-diazapentane and 2,4-Dinitro-2,4-diazahexane

Abstract: Binary phase diagrams for two mixtures of methylnitramine (1) + 2,4-dinitro-2,4-diazapentane (2) (eutectic temperature T E = 285.1 K, eutectic composition x 1 = 0.565) and methylnitramine (1) + 2,4-dinitro-2,4-diazahexane (2) (eutectic temperature T E = 280.3 K, eutectic composition x 1 = 0.653) were studied using differential scanning calorimetries (DSC). For both systems simple eutectic behavior was observed. The eutectic compositions were also determined using Gray's model and the fractional transformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…composition can be significantly improved using the method proposed by Matsuoka and Ozawa [31], often used in the literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. This method is based on the assumption that the eutectic fraction is defined as:…”
Section: Determination Of Solid-liquid Phase Diagrams (Slpd)mentioning
confidence: 99%
See 1 more Smart Citation
“…composition can be significantly improved using the method proposed by Matsuoka and Ozawa [31], often used in the literature [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. This method is based on the assumption that the eutectic fraction is defined as:…”
Section: Determination Of Solid-liquid Phase Diagrams (Slpd)mentioning
confidence: 99%
“…Recently, it has been reported that differential scanning calorimetry (DSC) technique allows more accurate and rapid characterisation of any kind of phase change [9,[15][16][17][18][19]. Thus, it seemed interesting to use the DSC technique for the determination of SLE of complex systems including the stabilizers diphenylamine, ethyl centralite, methyl centralite and their derivatives.…”
Section: Introductionmentioning
confidence: 99%